2020
DOI: 10.15376/biores.15.4.8403-8419
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of nematode-infected pinewood for mushroom cultivation and production of reducing sugar

Abstract: To improve the nematode-infected pinewood application value, an effective strategy was developed based on the cultivation of Flammulina velutipes to process the pinewood that was infected by the nematode Bursaphelenchus xylophilus. Different treatments were compared to determine the optimal method to obtain the highest yields of reducing sugars. The results showed that the cultivation of F. velutipes using the nematode-infected pine sawdust overcame the disadvantage of cultivation by using healthy pine sawdust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 21 publications
0
0
0
Order By: Relevance
“…It can be inferred from the results that the differences were due to the hydrolysis of some cellulose and hemicellulose that occurred during the period of infection by the pinewood nematode, which may have been caused by B. xylophilus infection. Previous studies have also reported that nematode-infected pine chips contain lower polysaccharide and lignin contents than healthy pine chips (Huan et al 2020). The chemical composition of healthy pine chips and nematode-infected pine chips was different depending on the steam explosion conditions.…”
Section: Effect Of Steam Explosion On the Chemical Composition Of Hea...mentioning
confidence: 83%
“…It can be inferred from the results that the differences were due to the hydrolysis of some cellulose and hemicellulose that occurred during the period of infection by the pinewood nematode, which may have been caused by B. xylophilus infection. Previous studies have also reported that nematode-infected pine chips contain lower polysaccharide and lignin contents than healthy pine chips (Huan et al 2020). The chemical composition of healthy pine chips and nematode-infected pine chips was different depending on the steam explosion conditions.…”
Section: Effect Of Steam Explosion On the Chemical Composition Of Hea...mentioning
confidence: 83%